Colonial copyright intellectual property in mandate Palestine - Birnhack, Michael D. (Oxford : Oxford University Press, 2012)
The history of colonial copyright is often told from the view of the colonizers. This study of the early roots of copyright in the British Empire provides a sophisticated theoretical framework, contextualizing early copyright law as a form of globalization and examining its impact on colonial affairs and modern law.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Copyright -- Palestine; Law -- Great Britain -- Colonies -- History -- 20th century; Palestine -- History -- 1917-1948.